Constitution and Constitutionalism in Indonesia - Rasji, Rasji; Howard, Christopher; Rukmana, Kevin; Anggitha, Fricila (CV. Rayyan Dwi Bharata, 2023)
As a constitutional state, of course the constitution is the basis for a state in carrying out state administration. This is also something that is happening in Indonesia considering that Indonesia is a constitutional state. In order for a constitution to move and function as it should, of course there needs to be constitutionalism which becomes a principle that can animate the constitution. This causes constitution and constitutionalism to be closely related. What's more, its implementation in Indonesia is very clear, namely with the restrictions on power that occur in Indonesia.